Consumers’ Perception of Private Brands:An Empirical Examination - Kokatnur, Shilpa S. (Indian Journal of Marketing, 2009)
The current Indian economy is witnessing the emergence of organized retail. It is growing at a faster pace and is expected to reach 10% from the current 4% of the total retail business. Retailers are expanding through variety of formats like supermarkets, convenience stores, hypermarkets, discount stores, specialty stores, and department stores. Many domestic business houses have entered this sector with ambitious plans. With the new FDI regime, foreign players are incisive of Indian partners to grab the potential of retail market in India. As competition is becoming stiff, retailers are working on new strategies to sustain in the market. One such strategy being private branding adopted by most of the retailers. Private brands are the most successful corporate brands in the world. Private branding is one of the strategic decisions of most retail organizations in recent years. They are either manufactured by the retailer or bought directly form the manufacturer, avoiding the intermediaries. Hence retailers have control over the marketing mix elements.